2022
DOI: 10.30541/v45i1pp.87-98
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Investment on Economic Growth in Pakistan

Abstract: This paper explores the role of public investment in the process of economic growth, in the context of Pakistan's economy, using the vector autoregressive approach (VAR). Based on theoretical considerations, the model also includes private investment and public consumption besides public investment. The results show that growth is largely driven by private investment and that no strong inference can be drawn from the effects of public investment and public consumption on economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
2

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 33 publications
5
44
1
2
Order By: Relevance
“…So, overall increase in public investment in Pakistan not only effect economic growth but also creates hurdles in the pace of development. In the case of Pakistan the public investment has great effect on economic growth, the provision of public investment raises the GDP (Ghani and Din, 2006).…”
Section: Public Investment Economic Growth and Pakistanmentioning
confidence: 99%
“…So, overall increase in public investment in Pakistan not only effect economic growth but also creates hurdles in the pace of development. In the case of Pakistan the public investment has great effect on economic growth, the provision of public investment raises the GDP (Ghani and Din, 2006).…”
Section: Public Investment Economic Growth and Pakistanmentioning
confidence: 99%
“…In this study, the authors use research variables to assess the interactive relationship between public investment and private investment and economic growth, along with other macro variables, according to studies done by Khan, M., & Kumar, M. (1997), Ghani, E., & Din, M. (2006), Phetsavong and Ichihashi (2012) or Zainah, P. (2009).…”
Section: Research Method Model and Datamentioning
confidence: 99%
“…Research results also indicated that both private investment and public investment contribute to economic growth. Ghani, E., & Din, M. (2006) have studied the impact of public investment on economic growth in Pakistan with using the vector autoregressive approach (VAR). The VAR consists of four variables including public investment, private investment, public consumption and GDP with data from 1973 to 2004.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ghani and Din (2006) [13] explored the relationship between public investment and economic growth for Pakistan economy. The study concluded that public investment had a negative, though insignificant impact on output.…”
Section: Literature Reviewmentioning
confidence: 99%